Role of the CHD7 chromatin remodeler protein in glioblastoma multiforme - Machado, Raquel Arminda Carvalho (2018)
Chromatin remodeler proteins exert an important function in promoting dynamic modifications in the chromatin architecture, rendering the transcriptional machinery available to the condensed genomic DNA. Due to this central role in regulating gene transcription, deregulation of these molecular machines may lead to severe perturbations in the normal cell functions. Loss-of-function mutations in the CHD7 gene, a member of the chromodomain helicase DNA-binding (CHD) family, are the major cause of the CHARGE syndrome in humans. The disease is characterized by a variety of congenital anomalies, including malformations of the craniofacial structures, peripheral nervous system, ears, eyes and heart. In this context, several studies have already shown the importance of CHD7 for proper function of the neural stem cells (NSCs). Interestingly, we found that CHD7 mRNA levels are upregulated in gliomas, when compared to normal brain tissue, therefore, we hypothesized that CHD7 might have a role in the pathogenesis of these tumors. To investigate the possible oncogenic role of CHD7 in glioblastoma (GBM), we adopted gain- and loss-of-function approaches in adherent GBM cell lines. Using CRISPR_Cas9 genome editing, we found that CHD7 deletion suppresses anchorage-independent growth and reduces spheroid invasion in human LN-229 cells. Moreover, deletion of CHD7 delayed tumor growth and improved overall survival in an orthotopic xenograft glioma mouse model. Conversely, ectopic overexpression of CHD7 in LN-428 and A172 cells was found to increase cell motility and invasiveness in vitro and LN-428 tumor growth in vivo. RNAseq analysis showed that alterations of CHD7 expression levels promote changes in several molecular pathways and modulate critical genes associated with cell adhesion and locomotion. However, the mechanisms underlying the effects of CHD7 overexpression in glioma tissue are still not understood. Here, we also generated recombinant plasmid with functional CHD7 promoter activity reported by luciferase assay. This powerful tool should enable future studies to determine the direct targeting relationship between different signal transduction pathways and CHD7 geneexpression. In summary, our findings indicate that GBM cells expressing a high level of CHD7 may exist and contribute to tumor infiltration and recurrence. Further studies should warrant important clinical-translational implications of our findings for GBM treatment.